Causality Relationship between GDP and Energy Consumption in Georgia, Azerbaijan and Armenia - Kalyoncu, Huseyin; Gürsoy, Faruk; Göcen, Hasan (International Journal of Energy Economics and Policy, 2012)
This research aims to investigate the relationship between energy consumption and economic growth in Georgia, Azerbaijan and Armenia during the period of 1995–2009. The Engle-Granger cointegration and Granger causality tests are used in order to analyse the causal relationship between energy consumption and economic growth. It is crucial to see the directions of causality between two variables for the policy makers. For Georgia and Azerbaijan it is found that these two variables are not cointegrated. In case of Armenia these two variables are cointegrated. Accordingly, causality analysis is conducted for Armenia. The research outcomes reveal that there is unidirectional causality from per capita GDP to per capita energy consumption for Armenia. Keywords: Economic growth; Energy consumption; Granger causality JEL Classifications: O43; C22